(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2025)
Found poetry can be constructed from participant transcripts in hermeneutic phenomenological research and from other sources. Two examples are given here, in a reflexive exploration addressing experiences of vicarious trauma, when working with clients who are at risk of dying. Ethics, trust and promises are considered in therapeutic work, and evaluated in the light of research into post-traumatic growth.